Chapter 16 The always-not-yet/always-already of voice perception Training towards vocal presence - Thomaidis, Konstantinos (Taylor & Francis, 2019)
As a first step towards tackling vocal presence as a matter of time, the proposed strategy is to attend to a particularly crucial moment in voice training: listening to one's own voice while in act of voicing. Even if voicers are trained to 'be in the moment' or to 'achieve presence,' they can only rely on post-voicing auditory feedback or pre-voicing kinaesthetic awareness; voice perception is always-not-yet there or always-already there. When asked about definitions of vocal presence or whether they have developed a definition of vocal presence for the specific purposes of their studio work, all interviewees admit the complexity or impossibility of the task. Vocal presence can move beyond the bounds of the individual body and physiological or psychological notions of tension and release. Jane Boston asserts that an advantageous starting point for training vocal presence is breath, as 'phonation depends on the appropriate manipulation of breath pressure and its conscious application for production of efficient soundwaves'.